Multiple Decrement Models in Insurance An Introduction Using R - Deshmukh, Shailaja Rajendra (Springer India : Imprint: Springer, 2012)
The book will serve as a guide to many actuarial concepts and statistical techniques in multiple decrement models and their application in calculation of premiums and reserves in life insurance products with riders and in pension and employee benefit plans as in these schemes, the benefit paid on termination of employment depends upon the several causes of termination. Multiple state models are discussed to accommodate the insurance products in which the payment of benefits or premiums is dependent on being in a given state or moving between a given pair of states at a given time, for example, disability income insurance model. The book also discusses stochastic models for interest rates and calculation of premiums for some products in this set up. The highlight of the book is usage of R software, freely available from public domain, for computations of various monetary functions involved in insurance business. R commands are given for all the computations.